Addition of Algebraic Expression

 

To add several positive like terms, let us follow the steps below

Step 1 : Obtain all like terms.

Step 2 : Find the sum of the numerical coefficients of all terms.

Step 3 : Write the required sum as a like term whose numerical coefficient is the numerical obtained in Step 2 and literal factor is same as the literal factors of the given like terms.

Examples:
1) Add 6xy, 15xy and 8xy.

Solution: 
6xy ---> coefficient 4 
15xy ----> coefficient 12
8xy -----> coefficient 3
Add all the coefficients ( 6+15+8 = 29).
Hence, 6xy + 15xy + 8xy = 29xy. 

2) Subtract 2x 2 + y 2 + 6xy from 4x 2 + 12xy – 3y 2 

Solution
=(4x 2 + 12xy – 3y 2 ) – (2x 2 + y 2 + 6xy)
= 4x 2 + 12xy – 3y 2 - 2x 2 - y 2 - 6xy
= 4x2 +12xy – 3y2 - 2x2 – y2 - 6xy 
= 2x 2 +6 xy – 4y 2